Characterisation of the P2Y14 receptor in the pancreas: control of vascular tone and insulin secretion - Alsaqati, Mouhamed (2014)
The P2Y14 receptor is the most recently identified member of the P2Y family of receptors for adenine and uridine nucleotides and nucleotide sugars. It is activated by UDP, UDP-glucose and its analogues, as well as the synthetic analogue MRS2690, which exhibits greater potency and selectivity at the P2Y14 receptor. The principle aim of this study was to investigate the functional expression of the P2Y14 receptor in porcine pancreatic arteries, and the signalling pathways underlying the vasoconstriction evoked by P2Y14 receptor agonists, together with an examination of the effects of UDP-glucose and MRS2690 on insulin secretion from the rat INS-1 823/13 β-cell line.